Combined application of cyanobacteria with soil fixing chemicals for rapid induction of biological soil crust formation. Issue 1 (2nd January 2017) - Park, Chan-Ho; Li, Xin-Rong; Jia, Rong-Liang; Hur, Jae-Seoun
ABSTRACT: Combined applications of cyanobacteria with soil fixing chemicals were investigated to generate artificially induced biological soil crust (BSC). Polyvinyl alcohol (PVA) and Tacki-Spray (TKS7) chemicals composed of bio-polysaccharides and tackifiers were examined under laboratory conditions. Following singular applications of chemicals, the mean weight diameter values of soil treated with TKS7 were 1.4–2.5 times higher than those of soil treated with PVA and thus TKS7 was selected for further tests for application with cyanobacteria ( Nostoc Vaucher ex Bornet & Flahault, Phormidium Kützing ex Gomont, and Scytonema arcangeli Bornet ex Flahault). Combined application of cyanobacteria and different concentrations of TKS7 enhanced soil aggregate stability, resulting in mean weight diameter values of 0.58–0.69 mm and was comparable to TKS7 singular application (0.18–0.40 mm). Surface hardness values were also highly improved by the combined application of cyanobacteria with TKS7 (4.5 MPa) compared to singular treatment of cyanobacteria (2.3 MPa). In addition, superabsorbent polymer (SAP) was applied as a water-holding material and nutrient supplement in soil. The SAP promoted cyanobacterial cell growth under dry conditions. Chlorophyll a content of soil was improved by the addition of SAP (CST1: 2.93 µg g −1 ) compared to singular treatment of cyanobacteria (C: 2.25 µg g −1 ). These results suggest that combined application of cyanobacteria with TKS7 and SAP can induce BSC formation faster than singular application of cyanobacteria. The novel method presented herein can be applied to restoration of degraded soils in arid and semiarid areas.